Analisis Tegangan Lebih Transien Impuls Pada Mixed Transmission Line (SUTT-SKTT) 150 KV Menggunakan Software ATP-EMTP - Oky Kurniawan; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The distribution of electrical power from the power plant to the center of the load on the transmission line can occur the electrical fault. This fault that often occurs is a transient overvoltage caused by a direct lightning stroke. Lightning stroke can cause the lightning impulses which are the dominant factor in generating the transient over voltages on 150 kV overhead lines compare to the high voltage cable lines. This investigation studied the effect of lightning stroke on the 150 kV mixed transmission lines using the ATP-EMTP (Alternative Transient Program – Electromagnetic Transient Program) software . The data analysis is carried out by simulating all line parameters and evaluating the transient overvoltage value on the transmission lines. It is shown that the highest transient overvoltage occurs when the lightning strikes on the ground static wires compared to when the lightning strikes on the phase wires. It is also shown that the use of the 150 kV mixed-lines can decrease the overvoltage caused by the direct lightning stroke. The installation of arresters on the transmission towers provides a significant reduction in over voltage caused by lightning stroke.Keywords : arrester, ATP-EMTP, lightning, mixed transmission lines, transient over voltage.